The impact of the methods, techniques, and strategies implemented by public high-school english teachers of the metropolitan área of San Salvador in the year 2016 - García, Luis Enrique
Nowadays, to speak English in the working world has stopped being just something desirable and it has turned into a mandatory language for progress in general terms. English has ecome the predominant language of business and has become an important tool in many areas. The knowledge and management of the above-mentioned language increases the possibilities of finding a good job, so today more than ever, it is essential to learn the English language. In the globalization era, the English language is an international language and a lingua franca that is now being used in most countries, including El Salvador, in which speaking English has become a need to apply for a job or get a scholarship abroad. Language teaching, as any other process, has the function of making students interact with one another; to make this happen, teachers must be highly qualified not only to develop certain contents or inculcate values and beliefs, but also to identify and correct the learning difficulties of the students so as to improve the English learning process. For this reason, English teachers should have a specialized academic education degree that allows them to apply methods, techniques, and strategies appropriately in every single class to develop and reinforce students’ abilities through the use of teaching materials and audiovisual resources needed to teach an English class.